A gas diffusion layer and a method for preparing the same

By adding carbon nanotube-UIO-66 composite material and hydrophobic agent to the carbon fiber substrate, a new gas diffusion layer was prepared, which solved the problem that traditional layer structures were difficult to take into account in high and low humidity conditions, and achieved improvement in conductivity and drainage performance and simplification of process.

CN116826093BActive Publication Date: 2025-03-04DONGFENG MOTOR GRP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310416728.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-18
Publication Date
2025-03-04
Estimated Expiration
2043-04-18

AI Technical Summary

Technical Problem

It is difficult for the traditional gas diffusion layer to take into account the performance of the membrane electrode under high humidity and low humidity conditions, and the production process is complicated and is not conducive to large-scale production.

Method used

Carbon fibers are used as the substrate, and conductive agents such as carbon nanotube-UIO-66 composite materials and hydrophobic agents such as a mixture of nickel sulfate and stearic acid are added, and a gas diffusion layer is obtained by mixing ball milling and hot pressing.

Benefits of technology

It achieves excellent conductivity and drainage performance of the gas diffusion layer, strong mechanical properties and small internal resistance, and can take into account the performance of the membrane electrode under high humidity and low humidity conditions, simplifying the process and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116826093B_ABST
    Figure CN116826093B_ABST
Patent Text Reader

Abstract

The present application relates to a gas diffusion layer and a preparation method thereof, and belongs to the field of fuel cell technology; the gas diffusion layer comprises carbon fiber, a conductive agent and a hydrophobic agent, the carbon fiber is distributed in a porous skeleton to form a carbon fiber skeleton, and the conductive agent and the hydrophobic agent are attached to the carbon fiber skeleton; the gas diffusion layer takes carbon fiber as a substrate, and adds a conductive agent and a hydrophobic agent, so that the conductivity and drainage performance of the GDL are more excellent, and it has stronger mechanical properties. Compared with the traditional GDL, it does not have a GDB layer and an MPL layer, which makes it thinner, and the internal resistance of the body and the internal resistance between it and the CCM are both smaller. When applied to a membrane electrode, the gas distribution during the operation of the membrane electrode is more reasonable, which broadens the operating range of the membrane electrode, and thus can take into account the performance of the membrane electrode at high humidity and low humidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel cell technology, and in particular to a gas diffusion layer and a preparation method thereof. Background Art

[0002] Hydrogen energy is a renewable and clean energy with the characteristics of high specific energy and environmental protection. Proton exchange membrane fuel cell is a device that can generate electricity using hydrogen energy. It is mainly composed of membrane electrode. Hydrogen and air are introduced into both sides of the membrane electrode to generate electricity, and the only product is water. The membrane electrode is mainly composed of a proton exchange membrane, a catalyst layer and a gas diffusion layer. The gas diffusion layer is mainly composed of a substrate layer and a microporous layer. The main component of the substrate layer is carbon paper, which plays the role of supporting the catalyst layer and distributing the gas. The microporous layer is mainly composed of a conductive agent, a pore-forming agent, a hydrophobic agent and a binder. It mainly plays the role of water management and reducing contact resistance, and it determines the performance of the gas diffusion layer.

[0003] At present, the structure of the traditional gas diffusion layer includes a base layer and a microporous layer. The preparation method is to coat the microporous layer slurry on carbon paper by scraping, screen printing, spraying, etc., and then heat it at high temperature to obtain the gas diffusion layer. If the membrane electrode made of the current gas diffusion layer needs to improve its performance at low humidity during operation, it usually needs to sacrifice its performance at high humidity, and vice versa. It is difficult to take into account the performance of the membrane electrode at both high and low humidity. Summary of the invention

[0004] The present application provides a gas diffusion layer and a preparation method thereof, which can take into account the performance of a membrane electrode at both high humidity and low humidity.

[0005] During the invention process, the inventors discovered that the thickness of the gas diffusion layer having a base layer and a microporous layer is relatively thick, resulting in a large contact internal resistance between the gas diffusion layer and the catalyst layer, and the distribution of gas will also be affected when the membrane electrode is in operation. This makes it difficult to balance the performance of the membrane electrode at high humidity and low humidity.

[0006] In a first aspect, the present application provides a gas diffusion layer, characterized in that the gas diffusion layer comprises carbon fibers, a conductive agent and a hydrophobic agent, the carbon fibers are distributed in a porous skeleton form to form a carbon fiber skeleton, and the conductive agent and the hydrophobic agent are attached to the carbon fiber skeleton.

[0007] As an optional embodiment, the conductive agent includes a carbon nanotube-UIO-66 composite material.

[0008] As an optional embodiment, the hydrophobic agent includes a first hydrophobic agent and a second hydrophobic agent, the first hydrophobic agent includes a mixture of nickel sulfate and stearic acid; the second hydrophobic agent includes polysiloxane.

[0009] As an optional embodiment, the mass ratio of the mixture of nickel sulfate and stearic acid is 1:(10-20); and / or

[0010] The polysiloxane includes at least one of poly(dimethylsiloxane), hexaethyldisiloxane, diethyldiethoxysiloxane, and hexaethylcyclotrisiloxane.

[0011] As an optional implementation, the mass ratio of the carbon fiber, the conductive agent and the hydrophobic agent is 1: (1-5): (30-60).

[0012] In a second aspect, the present application provides a method for preparing a gas diffusion layer, the method comprising:

[0013] The carbon fiber, the conductive agent and the hydrophobic agent are mixed and ball-milled to obtain a slurry;

[0014] The slurry is molded and hot-pressed to obtain a gas diffusion layer.

[0015] As an optional embodiment, the conductive agent includes a carbon nanotube-UIO-66 composite material; and the preparation method of the carbon nanotube-UIO-66 composite material includes:

[0016] The carbon nanotubes are activated and then blended with UIO-66 to obtain a carbon nanotube-UIO-66 composite material;

[0017] The diameter of the carbon nanotube is 0.2-5 μm;

[0018] The activated activator comprises dilute sulfuric acid, and the molar concentration of the dilute sulfuric acid is 0.05-0.15 mol / L;

[0019] The activation temperature is 35-45°C, and the activation time is 5-7h;

[0020] The mass ratio of the carbon nanotubes to UIO-66 is 1:(1-10);

[0021] The blending is carried out in a DMF solution, the blending temperature is 130-150° C., and the blending time is 4-8 hours.

[0022] As an optional embodiment, the preparation method of the hydrophobic agent comprises:

[0023] Mixing nickel sulfate and stearic acid in a solvent, and then mixing with a second hydrophobic agent, wherein the second hydrophobic agent includes polysiloxane, to obtain a hydrophobic agent;

[0024] The solvent includes ethanol;

[0025] The mass ratio of the nickel sulfate, stearic acid and solvent is 1: (10-20): (20-40);

[0026] The polysiloxane includes at least one of poly(dimethylsiloxane), hexaethyldisiloxane, diethyldiethoxysiloxane, and hexaethylcyclotrisiloxane.

[0027] As an optional embodiment, the mass ratio of the carbon fiber, the conductive agent and the hydrophobic agent is 1: (1-5): (30-60);

[0028] The grinding ball particle size of the mixed ball mill is 10-40 mm, the rotation speed of the mixed ball mill is 200-600 r / min, and the mixing ball milling time is 30-90 min.

[0029] As an optional embodiment, the step of molding and hot pressing the slurry to obtain a gas diffusion layer comprises:

[0030] The slurry is placed in a mold and then dried to obtain a primary product;

[0031] hot pressing the primary product to obtain a gas diffusion layer;

[0032] The drying temperature is 120-140°C, and the drying time is 1.5-2.5h;

[0033] The temperature of the hot pressing is 150-200° C., and the pressure of the hot pressing is 4-8t.

[0034] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0035] The gas diffusion layer provided in the embodiment of the present application is based on carbon fiber and is added with a conductive agent and a hydrophobic agent, so that the conductivity and drainage performance of the GDL are better, and it has stronger mechanical properties. Compared with the traditional GDL, it does not have a GDB layer and an MPL layer, which makes it thinner, and the internal resistance of the body and the internal resistance between the body and the CCM are both smaller. When applied to the membrane electrode, the gas distribution during the operation of the membrane electrode is more reasonable, which broadens the operating range of the membrane electrode, and thus can take into account the performance of the membrane electrode at high humidity and low humidity. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0037] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0038] Figure 1 A flowchart of a method provided in an embodiment of the present application;

[0039] Figure 2 This is a graph of the internal resistance of the gas diffusion layer provided in Example 1 and Comparative Example 1 of the present application after being made into a membrane electrode under 10% humidification conditions. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0041] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0042] Glossary: ​​MEA: membrane electrode, GDL: gas diffusion layer, MPL: microporous layer, GDB: substrate layer.

[0043] At present, the structure of the traditional gas diffusion layer includes a base layer and a microporous layer. The preparation method is to coat the microporous layer slurry on carbon paper by scraping, screen printing, spraying, etc., and then heat it at high temperature to obtain the gas diffusion layer. If the membrane electrode made of the current gas diffusion layer needs to improve its performance at low humidity during operation, it usually needs to sacrifice its performance at high humidity, and vice versa. It is difficult to take into account the performance of the membrane electrode at both high and low humidity.

[0044] The inventors found during the invention process that the thickness of the gas diffusion layer with the base layer and the microporous layer is relatively thick, resulting in a large contact internal resistance between the gas diffusion layer and the catalyst layer, and the gas distribution will also be affected during the operation of the membrane electrode, which makes it difficult to balance the performance of the membrane electrode at high humidity and low humidity. In addition, pore-forming agents are often used in the preparation of traditional gas diffusion layers, and high-temperature baking is required during the processing, which makes the process complicated and is not conducive to mass production.

[0045] Therefore, the inventor intends to develop a thinner gas diffusion layer to reduce the internal resistance of the entire membrane electrode and the internal resistance of the gas diffusion layer and the catalyst layer.

[0046] An embodiment of the present application provides a gas diffusion layer, characterized in that the gas diffusion layer includes carbon fibers, a conductive agent and a hydrophobic agent, the carbon fibers are distributed in a porous skeleton shape to form a carbon fiber skeleton, and the conductive agent and the hydrophobic agent are attached to the carbon fiber skeleton.

[0047] The gas diffusion layer is based on carbon fiber, with conductive agent and hydrophobic agent added to make the conductivity and drainage performance of GDL better, and it has stronger mechanical properties. Compared with the traditional GDL, it does not have GDB layer and MPL layer, which makes it thinner, and the internal resistance of the body and the internal resistance between it and CCM are smaller. When applied to the membrane electrode, the gas distribution during the operation of the membrane electrode is more reasonable, which expands the operating range of the membrane electrode, and thus can take into account the performance of the membrane electrode at high humidity and low humidity.

[0048] In some embodiments, the conductive agent includes a carbon nanotube-UIO-66 composite material. The special structure of the nanotube-UIO-66 composite material can form natural pores during the preparation of the GDL, which makes it unnecessary to add a pore-forming agent in the subsequent preparation process. Instead, a physical mixing process is used to form local pores, which not only makes the gas-conducting performance of the GDL more excellent, but also avoids the subsequent high-temperature baking process, making the process simpler and suitable for large-scale production.

[0049] In some embodiments, the hydrophobic agent includes a first hydrophobic agent and a second hydrophobic agent, wherein the first hydrophobic agent includes a mixture of nickel sulfate and stearic acid; and the second hydrophobic agent includes polysiloxane.

[0050] In some embodiments, the mass ratio of the mixture of nickel sulfate and stearic acid is 1:(10-20); and / or

[0051] The polysiloxane includes at least one of poly(dimethylsiloxane), hexaethyldisiloxane, diethyldiethoxysiloxane, and hexaethylcyclotrisiloxane.

[0052] The reason for using the first hydrophobic agent and the second hydrophobic agent in combination is that the polymeric ester acid hydrophobic agent and the silane hydrophobic agent can produce better hydrophobicity under different working conditions.

[0053] In some embodiments, the mass ratio of the carbon fiber, the conductive agent and the hydrophobic agent is 1:(1-5):(30-60).

[0054] The reason for controlling the mass ratio of carbon fiber, conductive agent and hydrophobic agent to be 1: (1-5): (30-60) is that this appropriate ratio can ensure that the gas diffusion layer has excellent hydrophobicity and conductivity at the same time, so that the two properties can achieve a balance.

[0055] like Figure 1 As shown, based on a general inventive concept, an embodiment of the present application further provides a method for preparing a gas diffusion layer, the method comprising:

[0056] S1. The carbon fiber, the conductive agent and the hydrophobic agent are mixed and ball-milled to obtain a slurry;

[0057] In some embodiments, the conductive agent includes a carbon nanotube-UIO-66 composite material; the preparation method of the carbon nanotube-UIO-66 composite material includes: activating the carbon nanotubes, and then blending them with UIO-66 to obtain the carbon nanotube-UIO-66 composite material.

[0058] Furthermore, the diameter of the carbon nanotubes is 0.2~5μm; the activation activator includes dilute sulfuric acid, and the molar concentration of the dilute sulfuric acid is 0.05~0.15mol / L; the activation temperature is 35~45°C, and the activation time is 5~7h; the mass ratio of the carbon nanotubes to UIO-66 is 1:(1~10); the blending is carried out in a DMF solution, the blending temperature is 130~150°C; and the blending time is 4~8h.

[0059] The reason for controlling the mass ratio of carbon nanotubes and UIO-66 to 1: (1-10) is that this ratio can make the gas diffusion layer have a better internal pipeline distribution. If the ratio is inappropriate, too small or too many pipelines will make the performance of the gas diffusion layer not optimal.

[0060] Specifically, in this embodiment, the carbon nanotubes are placed in dilute sulfuric acid for treatment, and then the carbon nanotubes are blended with UIO-66 to obtain a carbon nanotube-UIO-66 composite material.

[0061] In some embodiments, the preparation method of the hydrophobic agent includes: mixing nickel sulfate and stearic acid in a solvent, and then mixing with a second hydrophobic agent, wherein the second hydrophobic agent includes polysiloxane, to obtain a hydrophobic agent.

[0062] Furthermore, the solvent includes ethanol; the mass ratio of the nickel sulfate, stearic acid and solvent is 1: (10-20): (20-40); and the polysiloxane includes at least one of poly (dimethylsiloxane), hexaethyldisiloxane, diethyldiethoxysiloxane and hexaethylcyclotrisiloxane.

[0063] In some embodiments, the grinding ball particle size of the mixed ball mill is 10-40 mm, the rotation speed of the mixed ball mill is 200-600 r / min, and the mixing ball milling time is 30-90 min.

[0064] Specifically, in this embodiment, the first hydrophobic agent is first prepared: nickel sulfate is mixed with stearic acid and ethanol, and stirred at room temperature; then the second hydrophobic agent is slowly dropped into the first hydrophobic agent.

[0065] S2. The slurry is molded and hot-pressed to obtain a gas diffusion layer.

[0066] In some embodiments, the step of molding and hot pressing the slurry to obtain a gas diffusion layer comprises:

[0067] S2.1. Place the slurry in a mold and then dry it to obtain a primary product;

[0068] Furthermore, the drying temperature is 120-140° C., and the drying time is 1.5-2.5 hours.

[0069] S2.2. Hot-press the preliminary product to obtain a gas diffusion layer.

[0070] Furthermore, the temperature of the hot pressing is 150-200° C., and the pressure of the hot pressing is 4-8t.

[0071] Specifically, in this embodiment, carbon fiber and conductive agent are added to the hydrophobic agent, grinding balls are added to the mixed solution for ball milling, and a slurry with uniform particle size is obtained after the ball milling. The slurry is poured into a metal mold of 100mm*100mm*0.2mm, and the metal mold is placed in an oven to evaporate the solvent. The mold is then hot pressed on a hot press and taken out after the hot pressing to obtain a gas diffusion layer.

[0072] The substrate-free gas diffusion layer prepared by this method abandons the traditional GDB plus MPL structure and uses carbon fiber as the skeleton of the entire GDL, which makes the GDL have strong mechanical properties. At the same time, because there is no distinction between GDB and MPL, the subsequent processing adopts one-step hot pressing molding, and the process is simple. In addition, the use of carbon nanotube-UIO-66 composite material as a conductive agent further improves the conductivity of GDL, and the special structure of the conductive agent can form natural pores during the preparation of GDL, which makes it unnecessary to add pore-forming agents in the subsequent preparation process.

[0073] By analyzing and comparing the prepared GDL with the commercial GDL, it was found that the GDL prepared by this method has a smaller intrinsic internal resistance and lower contact internal resistance, and its mechanical properties such as tensile strength and elongation at break are also better than those of the commercial GDL. The GDL was loaded on CCM for performance testing, and it was found that the performance of the GDL prepared by this method was basically maintained at the same level as that of the commercial GDL, and showed better performance under low humidification conditions.

[0074] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0075] Example 1

[0076] A method for preparing a gas diffusion layer, the method comprising:

[0077] (1) Preparation of conductive agent

[0078] First, take 1g of carbon nanotubes with a diameter distribution of 1-2μm, add the carbon nanotubes to 20mL of dilute sulfuric acid with a concentration of 0.1mol / L, and stir on a magnetic stirrer at 100r / min and 40℃ for 1h.

[0079] After stirring, the carbon nanotubes were filtered to obtain carbon nanotubes, 4g UIO-66 (prepared in the laboratory) was added to the carbon nanotubes, and 25g DMF solution was added and poured into the reactor, and the reactor was placed in an oven, the temperature was set to 140°C, and the temperature was kept for 4 hours. After the reaction was completed, the conductive agent was filtered to obtain the conductive agent.

[0080] (2) Preparation of hydrophobic agent

[0081] First, prepare hydrophobic agent 1, mix 1g nickel sulfate with 10g stearic acid and 20g ethanol, and stir at room temperature; then slowly drop 10g hexaethyldisiloxane into hydrophobic agent 1. Then stir the hydrophobic agent with a magnetic stirrer and set aside.

[0082] (3) Preparation of gas diffusion layer

[0083] Take 1g of carbon fiber, 1g of conductive agent and 30g of hydrophobic agent and mix them. Add 5 grinding balls with a particle size of 10 mm into the mixture. Grind the mixture for 20 minutes at a speed of 200 r / min. After grinding, pour the slurry into a 100mm*100mm*0.2mm metal mold, put the metal mold into an oven to evaporate the solvent, and then heat press the mold on a hot press. The hot pressing temperature is 180℃ and the hot pressing pressure is set to 4t. After hot pressing, take it out to obtain a gas diffusion layer.

[0084] Example 2

[0085] A method for preparing a gas diffusion layer, the method comprising:

[0086] (1) Preparation of conductive agent

[0087] First, take 1g of carbon nanotubes with a diameter distribution of 0.2-1μm, add the carbon nanotubes to 20mL of dilute sulfuric acid with a concentration of 0.1mol / L, and stir on a magnetic stirrer at 100r / min and 40℃ for 1h.

[0088] After stirring, the carbon nanotubes were filtered to obtain carbon nanotubes, 3g UIO-66 (prepared in the laboratory) was added to the carbon nanotubes, and 20g DMF solution was added and poured into the reactor, and the reactor was placed in an oven, the temperature was set to 140°C, and the temperature was kept for 4 hours. After the reaction was completed, the conductive agent was filtered to obtain the conductive agent.

[0089] (2) Preparation of hydrophobic agent

[0090] First, prepare hydrophobic agent 1, mix 1 g of nickel sulfate with 15 g of stearic acid and 30 g of ethanol, and stir at room temperature; then slowly drop 15 g of a mixture of hexaethyldisiloxane and poly(dimethylsiloxane) into hydrophobic agent 1. Then stir the hydrophobic agent with a magnetic stirrer and set aside.

[0091] (3) Preparation of gas diffusion layer

[0092] Take 1 g of carbon fiber, 3 g of conductive agent and 40 g of hydrophobic agent and mix them. Add 3 g of grinding balls with a particle size of 20 mm into the mixture. Grind the mixture for 20 minutes at a speed of 300 r / min. After grinding, pour the slurry into a 100 mm*100 mm*0.2 mm metal mold, put the metal mold into an oven to evaporate the solvent, and then heat press the mold on a hot press. The hot pressing temperature is 180 ° C and the hot pressing pressure is set to 6t. After the hot pressing is completed, take it out to obtain a gas diffusion layer.

[0093] Example 3

[0094] A method for preparing a gas diffusion layer, the method comprising:

[0095] (1) Preparation of conductive agent

[0096] First, take 1g of carbon nanotubes with a diameter distribution of 2-5μm, add the carbon nanotubes to 40mL of dilute sulfuric acid with a concentration of 0.1mol / L, and stir on a magnetic stirrer at 100r / min and 40℃ for 1h.

[0097] After stirring, the carbon nanotubes were filtered to obtain carbon nanotubes, 5 g of UIO-66 (prepared in the laboratory) was added to the carbon nanotubes, and then 40 g of DMF solution was added and poured into the reactor, and the reactor was placed in an oven, the temperature was set to 140°C, and the temperature was kept for 8 hours. After the reaction was completed, the conductive agent was filtered to obtain the conductive agent.

[0098] (2) Preparation of hydrophobic agent

[0099] First, prepare hydrophobic agent 1, mix 1 g of nickel sulfate with 20 g of stearic acid and 40 g of ethanol, and stir at room temperature; then slowly drop 20 g of diethyl diethoxysiloxane into hydrophobic agent 1. Then stir the hydrophobic agent with a magnetic stirrer and set aside.

[0100] (3) Preparation of gas diffusion layer

[0101] Take 1 g of carbon fiber, 5 g of conductive agent and 40 g of hydrophobic agent and mix them. Add 5 g of grinding balls with a particle size of 20 mm into the mixture. Grind the mixture for 20 min at a speed of 400 r / min. After grinding, pour the slurry into a 100 mm*100 mm*0.2 mm metal mold. Put the metal mold into an oven to evaporate the solvent. Then, heat press the mold on a hot press. The hot pressing temperature is 180 ° C and the hot pressing pressure is set to 8 t. After hot pressing, take it out to obtain a gas diffusion layer.

[0102] Example 4

[0103] A method for preparing a gas diffusion layer, the method comprising:

[0104] (1) Preparation of conductive agent

[0105] First, take 1g of carbon nanotubes with a diameter distribution of 1-5μm, add the carbon nanotubes to 40mL of dilute sulfuric acid with a concentration of 0.1mol / L, place it on a magnetic stirrer for stirring at 100r / min and 40℃ for 1h.

[0106] After stirring, the carbon nanotubes were filtered to obtain carbon nanotubes, 10 g of UIO-66 (prepared in the laboratory) was added to the carbon nanotubes, and then 40 g of DMF solution was added and poured into the reactor, and the reactor was placed in an oven, the temperature was set to 140°C, and the temperature was kept for 8 hours. After the reaction was completed, the conductive agent was filtered to obtain the conductive agent.

[0107] (2) Preparation of hydrophobic agent

[0108] First, prepare hydrophobic agent 1, mix 1 g of nickel sulfate with 20 g of stearic acid and 40 g of ethanol, and stir at room temperature; then slowly drop 30 g of a mixture of diethyldiethoxysiloxane, hexaethylcyclotrisiloxane and poly(dimethylsiloxane) into hydrophobic agent 1. Then stir the hydrophobic agent with a magnetic stirrer and set aside.

[0109] (3) Preparation of gas diffusion layer

[0110] Take 1 g of carbon fiber, 5 g of conductive agent and 60 g of hydrophobic agent and mix them. Add 5 g of grinding balls with a particle size of 40 mm into the mixture. Grind the mixture for 20 minutes at a speed of 600 r / min. After grinding, pour the slurry into a 100 mm*100 mm*0.2 mm metal mold. Put the metal mold into an oven to evaporate the solvent. Then, heat press the mold on a hot press. The hot pressing temperature is 180 ° C and the hot pressing pressure is set to 8 t. Take it out after hot pressing to obtain a gas diffusion layer.

[0111] Comparative Example 1

[0112] Commercial GDL purchased from the market: (SGL 22BB).

[0113] The gas diffusion layers provided in Example 1 and Comparative Example 1 were cut into small pieces of 5 mm*5 mm, and the conductivity test, contact angle and mechanical property test were respectively carried out. The results are shown in the following table:

[0114]

[0115] It can be seen from the above table that the embodiment has a smaller in-plane resistance than the comparative example, and a larger contact angle indicates better hydrophobicity. The tensile strength and elongation at break are both greater than those of the comparative example, proving that the mechanical properties are more excellent. The inventors believe that this may be due to the use of carbon fiber as the skeleton of GDL.

[0116] The same CCM and the gas diffusion layers provided in Example 1 and Comparative Example 1 were used to assemble MEA. 2 The membrane electrode performance tests were carried out at 5 humidity levels of 10%, 25%, 50%, 75%, and 100%. The results are shown in the following table:

[0117]

[0118] It can be seen from the above table that, in Example 1, the voltage deviation value is small at a current density of 1000 mA / cm2 under different humidity conditions, which indicates that the GDL has a wider humidity application range and its performance is significantly better than that of Comparative Example 1 under low humidification conditions.

[0119] Attached Figure 2 Detailed description:

[0120] Attached Figure 2 The internal resistance curves of the gas diffusion layers provided in Example 1 and Comparative Example 1 after being made into membrane electrodes under 10% humidification conditions show that the internal resistance of the battery using Example 1 is much lower than that of Comparative Example 1. This is because the internal resistance of the GDL itself is relatively low, and the contact internal resistance of Example 1 is lower than that of Comparative Example 1. Therefore, the overall internal resistance of the MEA will be lower, which is beneficial to MEA power generation.

[0121] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0122] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items (individuals) or plural items (individuals). For example, "at least one of a, b, or c" or "at least one of a, b and c" can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or plural, respectively.

[0123] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A gas diffusion layer, characterized in that: The gas diffusion layer includes carbon fibers, a conductive agent and a hydrophobic agent, wherein the carbon fibers are distributed in a porous skeleton to form a carbon fiber skeleton, the conductive agent and the hydrophobic agent are attached to the carbon fiber skeleton, and the conductive agent includes a carbon nanotube-UIO-66 composite material.

2. The gas diffusion layer according to claim 1, characterized in that The hydrophobic agent includes a first hydrophobic agent and a second hydrophobic agent, wherein the first hydrophobic agent includes a mixture of nickel sulfate and stearic acid; and the second hydrophobic agent includes polysiloxane.

3. The gas diffusion layer according to claim 2, characterized in that: The mass ratio of the mixture of nickel sulfate and stearic acid is 1:(10-20); and / or The polysiloxane includes at least one of poly(dimethylsiloxane), hexaethyldisiloxane, diethyldiethoxysiloxane, and hexaethylcyclotrisiloxane.

4. The gas diffusion layer according to claim 1, characterized in that: The mass ratio of the carbon fiber, the conductive agent and the hydrophobic agent is 1:(1-5):(30-60).

5. A method for preparing a gas diffusion layer, characterized in that: The method comprises: The carbon fiber, the conductive agent and the hydrophobic agent are mixed and ball-milled to obtain a slurry; The slurry is molded and hot-pressed to obtain a gas diffusion layer; The conductive agent includes a carbon nanotube-UIO-66 composite material; and the preparation method of the carbon nanotube-UIO-66 composite material includes: The carbon nanotubes are activated and then blended with UIO-66 to obtain a carbon nanotube-UIO-66 composite material; The diameter of the carbon nanotube is 0.2-5 μm; The activated activator comprises dilute sulfuric acid, and the molar concentration of the dilute sulfuric acid is 0.05-0.15 mol / L; The activation temperature is 35-45°C, and the activation time is 5-7h; The mass ratio of the carbon nanotubes to UIO-66 is 1:(1-10); The blending is carried out in a DMF solution, the blending temperature is 130-150° C., and the blending time is 4-8 hours.

6. The method for preparing a gas diffusion layer according to claim 5, characterized in that: The preparation method of the hydrophobic agent comprises: Mixing nickel sulfate and stearic acid in a solvent, and then mixing with a second hydrophobic agent, wherein the second hydrophobic agent includes polysiloxane, to obtain a hydrophobic agent; The solvent includes ethanol; The mass ratio of the nickel sulfate, stearic acid and solvent is 1: (10-20): (20-40); The polysiloxane includes at least one of poly(dimethylsiloxane), hexaethyldisiloxane, diethyldiethoxysiloxane, and hexaethylcyclotrisiloxane.

7. The method for preparing a gas diffusion layer according to claim 5, characterized in that: The mass ratio of the carbon fiber, the conductive agent and the hydrophobic agent is 1: (1-5): (30-60); The grinding ball particle size of the mixed ball mill is 10-40 mm, the rotation speed of the mixed ball mill is 200-600 r / min, and the mixing ball milling time is 30-90 min.

8. The method for preparing a gas diffusion layer according to claim 5, characterized in that: The step of molding and hot pressing the slurry to obtain a gas diffusion layer comprises: The slurry is placed in a mold and then dried to obtain a primary product; hot pressing the primary product to obtain a gas diffusion layer; The drying temperature is 120-140°C, and the drying time is 1.5-2.5h; The temperature of the hot pressing is 150-200° C., and the pressure of the hot pressing is 4-8t.

Citation Information

Patent Citations

  • Gas diffusion layer for fuel cell and preparation method thereof

    CN112993265A

  • Processing technology of composite fiber fabric

    CN113355768A

  • Single-layer gas diffusion layer for proton exchange membrane fuel cell, preparation method and application

    CN114335564A